Comparing the frequency, antifungal susceptibility, and enzymatic profiles of the oral fungal composition in patients with and without Alzheimer's disease admitted to a neurology clinic - Golipoor, Mandana; Rafat, Zahra; Saberi, Alia; Roostaei, Davoud; Shabanpour, Amir-Mohammad (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundStudies have shown that changes in the frequency of oral microorganisms may play a key role in the development of Alzheimer's disease (AD). However, no research has been conducted on the oral fungal composition in AD-patients. The present study aimed to investigate the changes in the frequency of oral fungal composition, the antifungal susceptibility, and the enzymatic profiles of oral fungal composition in patients suffering from AD compared to non-AD individuals.Materials and methodsIn the present analytical cross-sectional study during 12 months, 76 hospitalized patients with AD were matched with 76 individuals without AD. A sterile serum physiology-moistened cotton-tipped swab was used to sample the mouth area. All swabs were cultured on Sabouraud Chloramphenicol Agar. Fungal identified were confirmed through the PCR-sequencing techniques. Enzyme activity index (EAI) for important pathogenic factors including proteinase, esterase and hemolysin was measured using relevant protocols. The susceptibility to 8 antifungal agents (nystatin, voriconazole, itraconazole, fluconazole, posaconazole, amphotericin B, 5-fluorocytosine, and caspofungin) against fungal strains obtained from AD-patients was evaluated according to the Clinical and Laboratory Standards Institute (CLSI) guidelines, document M38-A2 for filamentous fungi, and document M27-A4 for yeasts.ResultsThe results showed that compared to the non-AD individuals, the prevalence of oral fungal composition in AD group was 1.6 times higher. Candida albicans was the most common fungal species isolated from oral swab samples of AD group (n=53, 80%) and non-AD group (n=28, 40%), and the diversity of the oral fungal composition in AD-patients were lower than non-AD individuals. Among the 3 investigated virulence factors, a statistically significant difference was shown in terms of hemolysin activity level between the two studied groups (p<0.05) and the activity level of esterase and proteinase enzymes did not show a significant difference in the two studied groups (p>0.05). The results showed that almost all of the tested isolates were susceptible to nystatin, the most widely prescribed antifungal to treat superficial infections, and only 1.69 % (2/118) of the Candida isolates were resistant to this antifungal drug.ConclusionUnderstanding the changes in the frequency of oral fungal composition the antifungal susceptibility, and the enzymatic profiles of oral fungal composition in patients suffering from AD compared to non-AD individuals makes it possible to better understand the etiology of this disease.